Coal permeability evolution triggered by variable injection parameters during gas mixture enhanced methane recovery. (1st August 2022) - Zhou, Lijun; Zhou, Xihua; Fan, Chaojun; Bai, Gang
Abstract: Injection of gas mixture (CO2 /N2 ) into coal seam can both enhance methane recovery and reduce carbon dioxide emission. Coal permeability determines the mass transport speed, which acts an important index in evaluating gas injectability and methane recovery rate. To reveal effects of injected pressure, temperature and CO2 component in mixture on coal permeability evolution, the heat-fluid-solid coupling model in coal seam was proposed and series of simulations on gas mixture enhanced methane recovery were carried out. Results show that the continuous injected gas mixture replaces and drives methane toward the extraction borehole. The coal permeability is related to the heat or gas sorption induced coal swelling/shrinkage, gas pressure and geostress induced deformation, and coal mechanical properties. The coal permeability increases around the extraction borehole as CH4 pressure drops. There appears declining permeability zone as the arrive of CO2, resulting by the greater adsorption affinity than that of N2 and CH4 . The higher the injected pressure, the greater increase of permeability. Coal permeability decreases slightly with the injected temperature, however changes dramatically with the varying of injected CO2 component. The effects of injection parameters on permeability evolution are CO2 component, injection pressure, and injection temperature successively. Highlights: A heat-fluid-solid fully coupled model for gas mixture enhanced methane recovery was proposed. Coal permeability is dominated by strain change induced by heat, gas sorption, gas pressure geo-stress, and coal properties. Effects of injected CO2 component, injection pressure and temperature on coal permeability are comprehensively discussed.